Darwen Weavers Association Journal, 1941 (pg. 2) (United Kingdom, 1941)
1941 1939-1945 "Darwen Weavers Association Journal, 1941 (pg. 2)" [HFR0061b], 1941 Article on the Essential Works Order in the 'Darwen Weavers, Winders and Warpers Association Quarterly Journal', November 1941.